Cognitive Assessment of Children Who Are Deafblind: Perspectives and Suggestions for Assessments - Nicholas, Jude (Frontiers in Psychology, 2020)
The overall goal of a cognitive assessment is to improve communication, learning and quality of life for a child who is deafblind. This article will give a brief description and a perspective on different evaluation approaches as a basis for reliable cognitive and offer suggestions on how to improve the quality of a cognitive assessment in our clinical practice. The assessor should be aware of the limitations of norm-referenced tests if standardized normative measures are applied to evaluate the cognitive functions of a child who is deafblind. However, if engaging a child with deafblindness in a standardized normative assessment, special considerations and assessment concessions would be required. Furthermore, key issues on how to improve the quality of a cognitive assessment by affording multiple assessment pathways for cognitive assessments will be addressed. Particular attention is given to the following assessment approaches: multi-method, multi-informant assessment, ecological assessment, and dynamic assessment. The use of multiple assessment pathways is necessary to reveal the genuine cognitive abilities and potentials of a child with deafblindness.